The plasmepsin-piperaquine paradox persists in Plasmodium falciparum. - Breanna Walsh; Robert L Summers; Gabriel W Rangel; Laura M Hagenah; Sachel Mok; Manuel Llinás; David A Fidock; Dyann F Wirth; Selina Bopp (PLoS Pathogens)
Malaria remains a pressing global health challenge, with rising drug resistance threatening current treatment strategies. Partial resistance to dihydroartemisinin-piperaquine (DHA-PPQ) has emerged in Southeast Asia, particularly in Plasmodium falciparum strains from Cambodia. While artemisinin partial resistance is associated with mutations in kelch13, reduced PPQ sensitivity has been linked to increased copy numbers of the aspartic protease genes plasmepsin II and III and mutations in the chloroquine resistance transporter. In this study, we demonstrate the effective use of CRISPR-Cas9 technology to generate single knockouts (KO) of plasmepsin II and plasmepsin III, as well as a double KO of both genes, in two isogenic Cambodian parasites with varying numbers of plasmepsin gene copies. The deletion of plasmepsin II and/or III increased parasite sensitivity to PPQ. We explored several hypotheses to understand how an increased plasmepsin gene copy number might influence parasite survival under high PPQ pressure. Our findings indicate that protease inhibitors have a minimal impact on parasite susceptibility to PPQ. Additionally, parasites with higher plasmepsin gene copy numbers did not exhibit significantly increased hemoglobin digestion, differences in peptide composition, nor did they produce different amounts of free heme following PPQ treatment compared to wildtype (single copy) parasites. Interestingly, hemoglobin digestion was slowed in parasites with plasmepsin II deletions. We also found that culturing parasites with different plasmepsin II and III copies in amino acid-limited media had little impact on parasite sensitivity to high-dose PPQ. By treating parasites with modulators of digestive vacuole (DV) homeostasis, we found that changes in DV pH potentially affect their response to PPQ. Our research highlights the crucial role of increased plasmepsin II and III gene copy numbers in modulating response to PPQ and begins to uncover the molecular and physiological mechanisms underlying the contribution of plasmepsin II and III amplification to PPQ resistance in Cambodian parasites.